High Expression of Plasma Extracellular HSP90α is Associated With the Poor Efficacy of Chemotherapy and Prognosis in Small Cell Lung Cancer - Huang, Baoyue; Pan, Jinmiao; Liu, Haizhou; Tang, Yamei; Li, Shirong; Bian, Yingzhen; Ning, Shufang; Li, Jilin; Zhang, Litu (Frontiers in Molecular Biosciences, 2022)
Purpose: eHSP90α is closely related to tumor progression and prognosis. This study aimed to investigate the significance of eHSP90α in the response evaluation and prediction of small cell lung cancer. Methods: We analyzed the relationship between eHSP90α expression and clinicopathological features in 105 patients with small cell lung cancer. Univariate and multivariate analyses were used to determine the association of parameters and ratios with response assessment, progression-free survival (PFS), and overall survival (OS). Results: In SCLC patients, eHSP90α and NSE were positively correlated. The cutoff values of eHSP90α in OS, PFS, and response evaluation were 61.2ng/mL, 48.7ng/mL, and 48.7ng/mL, respectively. eHSP90α could better predict OS, PFS, and response evaluation (AUC OS 0.791, PFS 0.662, 0.685). Radiotherapy and eHSP90α were independent variables for effective chemotherapy through univariate and multivariate analysis. In contrast, radiotherapy, eHSP90α, NSE, and M stage were independent variables for OS. eHSP90α, and M stage were independent variables for PFS. Kaplan-Meier analysis showed that higher eHSP90α expression predicted poorer OS and earlier progression in patients. Conclusions: This study aims to provide new evidence for the efficacy response and prognostic assessment of SCLC. eHSP90α may be a better biomarker for SCLC.